2019
DOI: 10.1002/cncy.22201
|View full text |Cite
|
Sign up to set email alerts
|

Risk of malignancy in the various categories of the UK Royal College of Pathologists Thy terminology for thyroid FNA cytology: A systematic review and meta‐analysis

Abstract: Background. The UK Royal College of Pathologists Thy terminology for reporting thyroid FNAC cytology was first published in 2009, used throughout the United Kingdom and Ireland, in some parts of Italy and Switzerland, and elsewhere. There is no review of the literature or meta-analysis of the risk of malignancy (ROM) in the various categories of the UK Thy terminology. The study goal was to establish the published ROM for each Thy category and compare results with other existing terminology systems where simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 32 publications
4
36
1
Order By: Relevance
“…In a separate analysis at a single centre in Italy, 75 lesions with indeterminate FNAC underwent surgery with corresponding final histology; the PPV in TIR 3A was 4% and in TIR 3B was 48% . Comparing these results to both the meta‐analysis by Poller et al and our own results, there are notable differences in the reported malignancy rates; this may reflect environmental factors and different epidemiology of thyroid cancer between countries and local populations.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In a separate analysis at a single centre in Italy, 75 lesions with indeterminate FNAC underwent surgery with corresponding final histology; the PPV in TIR 3A was 4% and in TIR 3B was 48% . Comparing these results to both the meta‐analysis by Poller et al and our own results, there are notable differences in the reported malignancy rates; this may reflect environmental factors and different epidemiology of thyroid cancer between countries and local populations.…”
Section: Discussionsupporting
confidence: 59%
“…A recent systematic review and meta‐analysis assessed the risk of malignancy across different Thy categories . Thirteen articles were included, which totalled 3911 nodules.…”
Section: Discussionmentioning
confidence: 99%
“…A meta‐analysis of the risk of malignancy for patients with preoperative FNAC classified according to the UK Thy terminology showed comparable results to meta‐analyses of other internationally recognised reporting terminologies for pooled risk of malignancy for surgically excised nodules. The results for pooled risk of malignancy were Thy 1 12%, Thy 2 5%, Thy 3 22%, Thy 3a 25%, Thy 3f 31%, Thy 4 79% and Thy 5 98% . Hence, the performance of the UK Thy terminology appears similar to TBSRTC and other terminologies, although the range of reported Thy 1 rates in the published literature is perhaps higher than would be expected.…”
Section: Discussionmentioning
confidence: 72%
“…As no case of malignancy was found in our study, our data were not able to directly address this question. By way of comparison, a similar rate of malignancy was found in nodules classified as benign on cytology 30,32 . Unless there is a high level of clinical or US suspicion of thyroid cancer, no FNA should be performed in these nodules, and only clinical and sonographic follow‐up, or no follow‐up, is recommended 3,36,37 .…”
Section: Discussionmentioning
confidence: 86%